MATHEMATICAL RESILIENCE, HABITS OF MIND, AND SOCIOMATHEMATICAL NORMS BY SENIOR HIGH SCHOOL STUDENTS IN LEARNING MATHEMATICS: A STRUCTURED EQUATION MODEL - Samsul Maarif; Nelly Fitriani (IKIP Siliwangi and I-MES, 2023)
The process of learning mathematics is determined by cognitive aspects and requires an affective domain. The affective domain is essential in developing mathematical abilities to solve mathematical problems. This study aims to analyze the effect of mathematical resilience (RM) and habits of mind (HOM) on socio-mathematical norms (SMN) in mathematics learning. The research method used is quantitative, with survey techniques and structured inquiry models. The sample in this study was 100 high school students in the DKI Jakarta area. Data analysis was performed using the structured equation model (SEM) using SmartPLS software. This research uses eight items of mathematics resilience instrument, ten items of habits of mind instrument, and 12 items of socio-mathematical norm instrument. Each instrument has four alternative answers with a Likert scale. The results of the study concluded: 1) there is a positive impact of mathematical resilience on socio-mathematical norms; 2) there is a positive impact of habits of mind on socio-mathematical norms; 3) there is a positive impact of mathematical resilience on habits of mind; 4) there is a positive impact of mathematical resilience on sociomathematical norms mediated by habits of mind.